2017
DOI: 10.1093/ndt/gfx231
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell fractions correlate with lesions of diabetic kidney disease and predict loss of kidney function in Type 2 diabetes

Abstract: WBC fractions associate with morphometric lesions of DKD and predict RFL in individuals with Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
6
22
1
1
Order By: Relevance
“…The association of NLR with decreased eGFR might reflect the relationship of IFTA severity with worse damage. However, the level of NLR was dissociated from the glomerular lesions, which is consistent with the results of Wheelock et al 18 investigating the associations of NLR with morphometric parameters in 108 Pima Indians with DN. It is noteworthy that the median of eGFR at baseline in this study was 56.53 mL/min per 1.73 m 2 , and 86.7% (214) kidney biopsy reports showed scores of IFTA were 1-2, suggesting that the pathologic changes in DN was highly heterogeneous.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The association of NLR with decreased eGFR might reflect the relationship of IFTA severity with worse damage. However, the level of NLR was dissociated from the glomerular lesions, which is consistent with the results of Wheelock et al 18 investigating the associations of NLR with morphometric parameters in 108 Pima Indians with DN. It is noteworthy that the median of eGFR at baseline in this study was 56.53 mL/min per 1.73 m 2 , and 86.7% (214) kidney biopsy reports showed scores of IFTA were 1-2, suggesting that the pathologic changes in DN was highly heterogeneous.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, a recent study in 2017 has shown that NLR was inversely correlated with percentage of normally fenestrated endothelial cells and could predict the renal function loss in 108 Pima Indians and 941 Europeans with T2DM. 18 In our study, the NLR was significantly associated with IFTA and renal dysfunction. These findings suggested that the differences in NLR levels might reflect the inflammatory condition and result in the underlying renal injury, which finally leaded to the decline of e-GFR in DN.…”
Section: Discussionsupporting
confidence: 54%
“…These activated cells in turn produce pro-inflammatory cytokines that promote local tissue damage 6769 . A recent study in Pima Indians with type 2 diabetes found that lower lymphocyte and higher eosinophil and neutrophil fractions are also associated with early kidney structural damage, including increased GBM width and loss of glomerular endothelial cell fenestrations 66 . Examination of the kidney tissue revealed a higher proportion of WBC’s in the peripheral glomerular capillaries of participants with more advanced structural lesions, with frequent projections from the white cells touching endothelial cells within the glomerular capillary, suggesting signaling between these cells (Figure 3).…”
Section: Biomarkers Of Kidney Structurementioning
confidence: 98%
“…White blood cell counts and fractions are biomarkers of inflammation, which are linked to diabetes and its vascular complications 6365 , including a greater risk of ≥40% loss of GFR in a European type 2 diabetes cohort 66 . These findings are thought to be related, at least in part, to activation of white cells by advanced glycation end-products.…”
Section: Biomarkers Of Kidney Structurementioning
confidence: 99%
See 1 more Smart Citation